Business model maturity in management theory and practice – defining from an expert perspective - Niewiadomski Przemysław (Management)
Since many researchers and managers think about the essence, creation mechanisms and limits of the manufacturing model maturity, at this point, the author raises the question related to this issue: what dimensions (descriptions and desiderata) should be considered when conceptualizing this idea? The formulated question became a starting point and a point of conducting a creative synthesis, based, on the one hand, on a detailed analysis of the problem theory, and on the other hand – on the author’s own research. The above question and belief related to the existence of economic demand for results of application nature were the main inspiration to undertake research whose main purpose is to recognize: how the maturity of the business model is understood by selected experts operating in the Polish agricultural machinery sector?